Influence of fiber sources on weaned pigs' performance - Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1980)
Yorkshire pigs weaned at 5 to 6 weeks and averaging 25 lb were used to determine effects of diets with increased fiber from ground oats, wheat bran, alfalfa meal, or dried beet pulp on performance and diarrhea. The basal diet (corn-soybean meal fortified) contained 2.2% crude fiber; the diets using more fibrous feeds contained 3.9% fiber. Average daily gains on the basal and fiber diets were similar, as were the pounds of feed per pound of gain. Pigs fed the ground oats and wheat bran diets had slightly better fecal scores than those fed the other diets. None of the differences in performance or in daily fecal scores was statistically significant. Fiber added by ground oats, wheat bran, dried beet pulp, or alfalfa meal was neither beneficial nor detrimental to the performance of the weaned pigs.; Swine Day, Manhattan, KS, November 13, 1980
Keywords: Swine day; 1980; Kansas Agricultural Experiment Station contribution; no. 81-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 388; Swine; Fiber sources; Weaning; Performance